1999
DOI: 10.1126/science.286.5443.1362
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase p90 Rsk as an Essential Mediator of Cytostatic Factor Activity

Abstract: Persistent activation of p42 mitogen-activated protein kinase (p42 MAPK) during mitosis induces a "cytostatic factor" arrest, the arrest responsible for preventing the parthenogenetic activation of unfertilized eggs. The protein kinase p90 Rsk is a substrate of p42 MAPK; thus, the role of p90 Rsk in p42 MAPK-induced mitotic arrest was examined. Xenopus laevis egg extracts immunodepleted of Rsk lost their capacity to undergo mitotic arrest in response to activation of the Mos-MEK-1-p42 MAPK cascade of protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 32 publications
5
120
0
3
Order By: Relevance
“…Our studies with activating and inactivating Ras mutants provides strong evidence for this line of argument and show that BAD S112 is a target of Ras-mediated MEK/ERK activity ( Figure 5B). We could directly demonstrate that E 2 is able to activate p90 RSK1 (Figure 6,D and E), a downstream target of ERK1 and 2 (Zhao et al, 1996;Bhatt and Ferrell, 1999). Although the ability of E 2 to activate ERK remains controversial (Lobenhofer et al, 2000;Caristi et al, 2001;Song et al, 2002) due to unknown reasons, ERK activation seems to be important in the apoptotic re-sponse (Fang et al, 1999;Shimamura et al, 2000), perhaps through the regulation of BAD phosphorylation via p90 RSK .…”
Section: Estradiol Signals Through Two Pathways In Its Antiapoptotic mentioning
confidence: 83%
“…Our studies with activating and inactivating Ras mutants provides strong evidence for this line of argument and show that BAD S112 is a target of Ras-mediated MEK/ERK activity ( Figure 5B). We could directly demonstrate that E 2 is able to activate p90 RSK1 (Figure 6,D and E), a downstream target of ERK1 and 2 (Zhao et al, 1996;Bhatt and Ferrell, 1999). Although the ability of E 2 to activate ERK remains controversial (Lobenhofer et al, 2000;Caristi et al, 2001;Song et al, 2002) due to unknown reasons, ERK activation seems to be important in the apoptotic re-sponse (Fang et al, 1999;Shimamura et al, 2000), perhaps through the regulation of BAD phosphorylation via p90 RSK .…”
Section: Estradiol Signals Through Two Pathways In Its Antiapoptotic mentioning
confidence: 83%
“…Many studies showed that intermittent hypoxia might have the cardioprotective effects similar to those observed in ischemic preconditioning [2][3][4][5][6][7][8]. A number of studies have attempted to define the mechanisms of this phenomenon and several potential factors have been proposed to be involved in the protective mechanism afforded by intermittent hypoxia [3,[5][6][7][9][10][11], however, the precise mechanisms underlying the protective effects of intermittent hypoxia on ischemic hearts are far from clear.…”
Section: Intermittent Hypoxia Attenuates Ischemia/reperfusion Inducedmentioning
confidence: 99%
“…Among many substrates for MAP kinases, p90 rsk was the first to be discovered [3]. In Xenopus oocytes, the main effects of MAP kinase, including S phase suppression, MII arrest maintenance, and spindle formation regulation, are mediated by p90 rsk [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the following: (1) increased pyrimidine nucleotide synthesis by activating carbamoyl phosphate synthetase II, 60 (2) activation of transcription by phosphorylation of transcriptional factors 61 and histone H3 and HMG-14, 62 (3) stimulation of translation through phosphorylation of eukaryotic initiation factor 4E, 63 and (4) promotion of DNA replication by increasing expression of cyclin D1. 64 RSK, which is activated directly by ERK1/2 phosphorylation, with the involvement of PDK1 (3-phosphoinositide-dependent protein kinase 1), plays an essential role in the MAPK signaling pathway regulating cell survival and the cell cycle.…”
Section: The Mapk-rsk-c/ebp␤ Cascade Signals Cell Survivalmentioning
confidence: 99%